É doce, mas não é mole, não!: Representações sociais dos canavieiros alagoanos sobre o processo de “modernização” agrícola - Lima, José Rodolfo Tenório (2020)
Agricultural modernization through the mechanization of harvest presents itself as an expanding reality in the sugarcane fields of Brazil. The substitution of manual labor for machines has direct implications on work processes. Much is already known about what modernization is from a business perspective – for it is the entrepreneurs themselves who modernize – and what impacts the hegemonic ways of implementing it have on workers; but little is known about the meaning of modernization for subjects who are directly impacted by such actions. Therefore, the question that leads the research is: How do the subjects linked to the sugarcane world interpret and attribute meaning to the process of agricultural modernization that has been occurring in the sugar cane fields of Alagoas? The methodological path of the research has its predominance in the qualitative approach. However, it has also mobilized quantitative strategies when it was necessary. The research field took place in the state of Alagoas and the microregion of São Miguel dos Campos was the chosen territory. Within this micro-region, it was chosen as a research strategy to pick a production unit to carry out a case study. The survey data was collected from interviews (31 in total), field trips, access to government documents and databases, and entities representing the sector. To carry out the analysis, the collected and/or constructed data was compared and contrasted from the primary and secondary sources with the selected reference bibliography. The Theory of Social Representations was the theoretical choice made to help in understanding the subjectivities of workers on the modernization that took place in the sugarcane fields. From the outset, the representations are social, as they are developed from the context in which the subjects are inserted. Given this premise, three levels were investigated: national / regional, state and local. For the national / regional context, the exclusionary modernization process was identified, as the changes, resulting from the technological incorporation that allow the mechanization of work processes, have generated a great reduction in manual labor. In the local context, Alagoas, there is a type of modernization here called retarded, since archaic and modern go hand in hand. Finally, in the local context, the plant chosen for the case study presented itself as the most mechanized in the state. From this context, the investigated subjects positively represent modernization as an event that has enabled: a) better working conditions; b) higher yields; and c) greater professional development. However, the same event also presented, on the part of the interviewed subjects, a negative side, linked to the enormous unemployment that the technological incorporation generates. Thus, this type of representation was here called “rapadura”, because the popular saying that tries to express the multidimensionality of phenomena was used here: it is sweet, but it is not soft!. “Sweet” for a few and hard for many. Oxygenating the debate involving the world of sugarcane work based on the understanding of those directly involved in the modernization process is the contribution expected by the research.